(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The social community websites are new task for private safety, specifically while a person’s personal facts is discovered in contents published via means of others, inclusive of pictures with individuals. The fast improvement of numerous online social networks (OSNs) makes it unprecedentedly notable to share pictures online which lead OSNs as a main network to share images online. The unlawful task on the online contents include misusing of those pictures extensively. Because of this situation, finding the initial place and the propagation route of an online photograph are important for lots of forensic applications. In the proposed machine, a easy powerful method to determine the photograph starting place via way of means of exploiting the unique traces left via way of means of the various OSN operations. To this end, it first conducts a complete have a look at at the manipulations that numerous OSNs perform on uploaded images. It develops a machine to support customers collaborative private safety via way of means of permitting multiple customers to together manipulate the get admission to their non-public data.